Association between SKIV2L polymorphism rs429608 and age-related macular degeneration: A meta-analysis. (4th May 2017) - Shuai, Ping; Ye, Zimeng; Liu, Yuping; Qu, Chao; Liu, Xiaoqi; Luo, Huaichao; Feng, Xiaoyun; Li, Xiulan; Shi, Yi; Gong, Bo
ABSTRACT: Purpose : This study was conducted to comprehensively evaluate the potential association of SKIV2L polymorphism rs429608 with age-related macular degeneration (AMD) through a meta-analysis. Methods : We performed a literature search in EMBASE, PubMed, Web of Science, and the Chinese Biomedical Database for AMD genetic studies published before August 30, 2015. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated for single-nucleotide polymorphisms (SNPs) using fixed-effect models or random effect models according to between-study heterogeneity. Publication bias analyses were conducted using Egger's test. Results : A total of five studies from published articles were included, and a total number of 2789 AMD cases and 3451 healthy controls were tested in this meta-analysis. The results demonstrated that SKIV2L rs429608 is associated with AMD under allelic model (A vs. G; OR = 0.52, 95% CI 0.44–0.62, p < 0.001), heterozygous model (AG vs. GG; OR = 0.51; 95%CI, 0.38–0.68; p < 0.001; PQ = 0.48; I 2 = 0) and dominant model (AA+AG vs. GG; OR = 0.49; 95%CI 0.37–0.65; p < 0.001; PQ = 0.44; I 2 = 0), but not under other genetic models. Conclusions : This meta-analysis showed that SKIV2L rs429608 was statistically associated with AMD and it might exert a protective effect on AMD. Further investigations are needed to validate the association and confirm the role of SKIV2L in AMD.